The implication of school culture on building a cohesive pluralistic society: Evidence from Lebanon. (July 2019) - Baytiyeh, Hoda
Pluralistic societies are generally characterised by weak national cohesiveness, increasing the risk of political tension and violent conflict; for communities from diverse religious or ethnic backgrounds, peaceful coexistence alone is insufficient to build the social cohesion needed for sustainable development and lasting peace. As an effective environment for advancing intercultural dialogue, mutual understanding and positive interaction through active participation in learning activities, schools can form a part of a comprehensive strategy to enhance social cohesion in pluralistic societies. Using Lebanon as a case study, this article shows how decades of political and socioeconomic injustice in combination with poor education policies have perpetuated the dominance of a monocultural school climate, leaving Lebanese society divided and vulnerable to violence and conflict. Although education reforms have focused on nation building and nationalism, these have failed to promote a multicultural school climate, social cohesion or national identity. Educating students in this climate has prevented intercultural interaction and dialogue, instead reinforcing intragroup solidarity and intergroup competition and leading in turn to poor social cohesion.